Improving the quality of educational services by relying on information technology services: a case study in Al-Awael Private Schools group using qualitative data analysis - M. Abdullah Al- Ta'e , Adel; Tyb Fathee, Abd-Alaziz (Journal of College of Education, 2020)
The current research aims to highlight the importance of using Information Technology (IT) services for the sack of improving educational services. The research focuses of three main IT services, which are applications, support and consultation and data storage and security. We argue that the quality of educational  services in schools depends on their accredited IT services, assuming that these services have many dimensions which have no statistical impact on improving the quality. A total of 317 valid questionnaire were used for data analysis with AMOS software. The paper is expected to help increase and support the quality educational services in some private primary schools through offering accredited IT services.